A longitudinal exploratory investigation of innovation systems and sustainability maturity using case studies in three industries. Issue 4 (7th June 2019) - Abraham, Thomas; Dao, Viet T.
Abstract : Purpose: Sustainability innovation systems (SIS) refer to the investment in information systems (IS) to enable business sustainability within stages of sustainability maturity. A prior framework proposes that the roles played by IS to support sustainability depend on the stage of sustainability maturity achieved. The purpose of this paper is to empirically examine these propositions. Design/methodology/approach: This study conducts longitudinal case studies of six companies across three industries. Data were collected from the companies' Global Reporting Initiative (GRI) reports over a six-year period from 2009 to 2015. Findings: The study provides initial empirical support for the proposition of the SIS framework that companies follow a staged path to sustainability maturity and that IS play specific roles as companies mature. Research limitations/implications: The findings encourage future research to take a longitudinal and holistic view of sustainability and IS. Future research could also collect a more comprehensive data set for statistical analysis. Practical implications: The study provides guidelines for practitioners in making decisions about companies' investments in IS for sustainability, particularly within individual stages of sustainability maturity. Social implications: The study goes beyond environmental sustainability to empirically show that companies are deploying IT assets for social sustainability too. Originality/value: The multiple-longitudinal case study approach provides an intimate understanding of companies' actual usage of IS resources to enable sustainability. The study is also among the very early research using GRI reports for research on IS and sustainability, showing that these reports are a rich secondary data source for IS scholars.